ANALISIS SPASIAL PENCEMARAN LOGAM BERAT SEBAGAI DAMPAK TEMPAT PEMBUANGAN AKHIR SAMPAH KOTA AMBON PADA DAS WAI YORI DI NEGERI PASSO - Santoso Santoso; Johanis P Haumahu; Maimuna L Habi (Universitas Pattimura, 2016)
This study aims to determine the water quality, to identify the level of contamination of heavy metals Pb, Cd, Cu and Fe in the Wai Yori watershed due to the pollution from leachate from the Waste Landfill Ambon City, as well as to advise the managers of Waste Landfill and Municipal Government of Ambon. The study used survey method by sampling water and soil for analysis of heavy metals Pb, Cd, Cu and Fe. The sampling was intended to determine the levels of heavy metal pollution that contaminate the Wai Yori watershed. Water samples were analyzed in the laboratory of Research and Industrial Standard Institution Ambon, Jl. Kebun Cengkeh, the city of Ambon, while the soil samples were analyzed at the Forensic Laboratory Faculty of Science Halu Oleo University, Southeast Sulawesi. The results of this research showed that the amount of heavy metals contained in the sample and then was compared with the critical limit standard level. For heavy metal analysis results of water samples was compared to the critical limit of water according to the Ministry of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010. The results of the analysis of water samples were compared to the standard range of heavy metals as contaminants in the soil according to the Ministry of State for Population and Environment of Indonesia, and Dalhousie University, Canada (1992). The Pb content was as much as 0.01 ppm, Cd as much as 0.0003 ppm, 2 ppm Cu and 0.3 ppm Fe, and all samples contained metals below the standard values.